3D Microstructures: Transparent, Compliant 3D Mesostructures for Precise Evaluation of Mechanical Characteristics of Organoids (Adv. Mater. 25/2021). Issue 25 (22nd June 2021) - Ryu, Hanjun; Park, Yoonseok; Luan, Haiwen; Dalgin, Gokhan; Jeffris, Kira; Yoon, Hong‐Joon; Chung, Ted S.; Kim, Jong Uk; Kwak, Sung Soo; Lee, Geumbee; Jeong, Hyoyoung; Kim, Jihye; et al.
Abstract : Methods for mechanical assembly can form structures with elaborate 3D configurations, and broad potential applications in advanced microsystems technologies. In article number 2100026, John D. Finan, John A. Rogers, and co‐workers demonstrate soft, transparent 3D structures designed to gently constrain organoids for studies of their mechanical properties. Measurements reveal that the effective moduli of these systems depend on age and exposure to drugs.